2008
DOI: 10.1128/mcb.02154-07
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte Nuclear Factor 4α Contributes to Thyroid Hormone Homeostasis by Cooperatively Regulating the Type 1 Iodothyronine Deiodinase Gene with GATA4 and Krüppel-Like Transcription Factor 9

Abstract: Type 1 iodothyronine deiodinase (Dio1), a selenoenzyme catalyzing the bioactivation of thyroid hormone, is highly expressed in the liver. Dio1 mRNA and enzyme activity levels are markedly reduced in the livers of hepatocyte nuclear factor 4␣ (HNF4␣)-null mice, thus accounting for its liver-specific expression. Consistent with this deficiency, serum T 4 and rT 3 concentrations are elevated in these mice compared with those in HNF4␣-floxed control littermates; however, serum T 3 levels are unchanged. Promoter an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 73 publications
4
31
0
Order By: Relevance
“…Intermediary coregulators may be involved in the functional interaction between KLF9 and HNF4a. For example, a recent study showed that GATA4 forms a complex with KLF9 and HNF4a, and this interaction is important for activating genes involved in thyroid hormone homeostasis (Ohguchi et al, 2008). Taken together, our study revealed a novel role for KLF9 that it regulates CYP2D6 expression by enhancing HNF4a transactivation of CYP2D6 promoter activity.…”
Section: Discussionsupporting
confidence: 49%
“…Intermediary coregulators may be involved in the functional interaction between KLF9 and HNF4a. For example, a recent study showed that GATA4 forms a complex with KLF9 and HNF4a, and this interaction is important for activating genes involved in thyroid hormone homeostasis (Ohguchi et al, 2008). Taken together, our study revealed a novel role for KLF9 that it regulates CYP2D6 expression by enhancing HNF4a transactivation of CYP2D6 promoter activity.…”
Section: Discussionsupporting
confidence: 49%
“…Immunoprecipitation and Immunoblot Analysis-The methods for cell fractionation and immunoprecipitation were described previously (35)(36)(37)(38). Immunoblots were visualized by chemiluminescence using Super Signal West Dura Extended Duration Substrate (Thermo Fisher Scientific), and luminescent images were analyzed by ImageQuant LAS 4000mini (GE Healthcare).…”
Section: Methodsmentioning
confidence: 99%
“…For genome-wide transcription analysis, a GeneChip Mouse Genome 430 2.0 array (Affimetrix) was used as described previously (23).…”
Section: Antibodiesmentioning
confidence: 99%